Spelling Forms in Competition The Case of -ise vs. -ize - Calle-Martín, Javier (Cambridge, 2021)
One of the problems of English spelling is the dual representation of the so-called ‘eyes’-words, rendered in discourse as -ise and -ize, both with high-frequency verbs such as modernise/modernize and rare coinages, as in burglarise/burglarize, etc. Eyes-words have historically evolved from two different language systems as two different forms with the same meaning, which have eventually come to coincide in their use in English with competing orthographic forms. The present paper first assesses the origin and development of the competition of these forms in the history of English from their introduction into English to their current configuration in British and American English; and then analyses their distribution in 13 varieties of English worldwide from the perspective of diatopic and text type variation. The study concludes, on the one hand, that the adoption of -ize in American English was an early 19th-century phenomenon while -ise spread in British English in the late 20th century; and, on the other, that the dissemination of -ize is constantly on the rise in many varieties, and the growing Americanisation of English, among others, is taken to be the most decisive element factor.
Keywords: Inglés - Ortografía; English spelling; British English; American English